1991
DOI: 10.1104/pp.95.4.1214
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Leaves Contain Multiple Lipoxygenases

Abstract: Chromatofocusing of soybean (Glycine max L.) leaf lipoxygenases revealed three distinct peaks of activity. Based on their isoelectric points (pis), pH optima, and mutant analysis it appears that the leaf isozymes are different from those described from mature soybean seed. At least one leaf lipoxygenase appears to differ from those found in hypocotyls. The pis of the main bands of the three leaf lipoxygenase peaks are 6.67, 5.91, and 5.67. The pH optima curves of three active fractions exhibit peaks at pH 6.2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Western blotting was performed as described by Wang and Hildebrand (1987) using rabbit polyclonal antibodies raised against soybean leaf peak 3 LOX (Grayburn et al, 1991). Fifty micrograms of the protein extracted from tobacco leaves were analyzed on a 10% SDS gel and probed with polyclonal antibodies raised against soybean leaf peak 3 LOX isozyme.…”
Section: Electrophoresis and Western Blottingmentioning
confidence: 99%
“…Western blotting was performed as described by Wang and Hildebrand (1987) using rabbit polyclonal antibodies raised against soybean leaf peak 3 LOX (Grayburn et al, 1991). Fifty micrograms of the protein extracted from tobacco leaves were analyzed on a 10% SDS gel and probed with polyclonal antibodies raised against soybean leaf peak 3 LOX isozyme.…”
Section: Electrophoresis and Western Blottingmentioning
confidence: 99%
“…Vol. 107, 1995 In soybean leaves, total lipoxygenase protein and activity have been reported to vary with respect to leaf size (Hildebrand et al, 1988;Altschuler et al, 1989;Grayburn et al, 1991). Because soybean leaves contain multiple lipoxygenase isozymes, variation in total lipoxygenase protein and activity during Ieaf development probably results from changes in individual lipoxygenase isozymes, but the relationship of individual lipoxygenase isozyme levels to leaf age has not been established.…”
mentioning
confidence: 99%
“…Multiple lipoxygenase isozymes also occur in soybean leaves. Grayburn et al (1991) used chromatofocusing to separate three distinct peaks of lipoxygenase activity in extracts from soybean leaves. On the basis of physical and kinetic characterizations of the three leaf lipoxygenases, Grayburn et al (1991) concluded that the soybean leaf lipoxygenase isozymes are distinct from the isozymes found in seeds and that at least one of the leaf isozymes is different from the lipoxygenase isozymes found in hypocotyl/radicle axes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lipoxygenase activity in the leaves was determined colorimetrically (Grayburn et al, 1991). 29.9ml of linoleic acid was taken in 100ml volumetric flask and maintained at 30 0 C using hot water bath.…”
Section: Estimation Of Lipoxygenase Activitymentioning
confidence: 99%